An Analysis of Communication Patterns: A Method for Discriminating Leader and Subordinate Roles - Watson, Kathleen M. (Academy of Management Journal, 1982)
In this laboratory study of interaction patterns within leader-subordinate goal setting dyads, the hypothesis of role differences was supported. Leaders showed resistance to and subordinates showed compliance with each others' attempts to control the relationship. Leaders exercised multiple relationship options, in contrast with the subordinates' more structured responses.